Academic employees' green behaviour as praxis for bolstering environmental sustainable development: A linear moderated mediation evaluation. (25th April 2022) - Fawehinmi, Olawole; Yusliza, Mohd Yusoff; Ogbeibu, Samuel; Tanveer, M. Imran; Chiappetta Jabbour, Charbel Jose
Abstract: There have been calls for organisational employees across developed and emerging economies to be more responsible towards the environment because of the heightened level of devastation in the ecosystem due to human actions. This study examines the influence of environmental concern on employee green behaviour (EGB) through the mediation of attitude, perceived behavioural control (PBC), and environmental knowledge. SmartPLS 3 software was used to analyse the relationships from 425 valid responses. The findings of our study show that environmental concern, attitude, and PBC positively predict the EGB of academics. Attitude and PBC act as complimentary mediators of the relationship between environmental concern and EGB. Equally, a linear moderated mediation analysis shows that environmental concern amplifies the link between PBC and EGB. Furthermore, an importance‐performance map analysis (IPMA) provides evidence that suggests that though employees' attitude is a less important predictor of EGB when compared with environmental concern, their respective degree of performance is equal to each other. Furthermore, this study offers substantive insights into the multiple roles of environmental concern in influencing employee green behaviour among academics in higher education institutions (HEIs). Policy implications and future research directions for environmental sustainability are discussed.